Decomposition of multifunctionalized α-alkoxyalkyl-hydroperoxides derived from the reactions of Criegee intermediates with diols in liquid phases. Issue 19 (4th May 2022) - Endo, Yasuyuki; Sakamoto, Yosuke; Kajii, Yoshizumi; Enami, Shinichi
Abstract : The ozonolysis of alpha-terpineol with C3 –C5 diols produced multifunctionalized ROOHs that decomposed into hemiacetals and H2 O2 in acidic aqueous organic media. Abstract : The oxidation of volatile organic compounds in the atmosphere produces organic hydroperoxides (ROOHs) that typically possess not only –OOH but also other functionalities such as –OH and –C(O). Because of their high hydrophilicity and low volatility, such multifunctionalized ROOHs are expected to be taken up in atmospheric condensed phases such as aerosols and fog/cloud droplets. However, the characteristics of ROOHs that control their fates and lifetimes in liquid phases are poorly understood. Here, we report a study of the liquid-phase decomposition kinetics of multifunctionalized α-alkoxyalkyl-hydroperoxides (α-AHs) that possessed an ether, a carbonyl, a hydroperoxide, and two hydroxy groups. These ROOHs were synthesized by ozonolysis of α-terpineol in water in the presence of 1, 3-propanediol, 1, 4-butanediol, or 1, 5-pentanediol. Their decomposition products were detected as chloride anion adducts by electrospray mass spectrometry as a function of reaction time. Experiments using H2 18 O and D2 O revealed that hemiacetal species were α-AH decomposition products that further transformed into other products. The result that the rate coefficients ( k ) of the decomposition of C15 α-AHs increased exponentially from pH 5.0 to 3.9 was consistent with an H + -catalyzed decomposition mechanism. The temperature dependence of k and an Arrhenius plot yielded activation energies ( E a ) of 15.7 ± 0.8, 15.0 ± 2.4, and 15.9 ± 0.3 kcal mol −1 for the decomposition of α-AHs derived from the reaction of α-terpineol CIs with 1, 3-propanediol, 1, 4-butanediol, and 1, 5-pentanediol, respectively. The determined E a values were compared with those of related ROOHs. We found that alkyl chain length is not a critical factor for the decomposition mechanism, whereas the presence of additional –OH groups would modulate the reaction barriers to decomposition via the formation of hydrogen-bonding with surrounding water molecules. The derived E a values for the decomposition of the multifunctionalized, terpenoid-derived α-AHs will facilitate atmospheric modeling by serving as representative values for ROOHs in atmospheric condensed phases.